Arkeologi Kepulauan Maluku - Wattimena, Lucas (Kapata Arkeologi, 2013)
Archaeological cultural resources in the Maluku Islands consist of a variety of aspects, including Prehistoric, Historic, Islamic, colonial and Ethnoarchaeology. These aspects are categorized in helping the mapping of archaeological research in the Maluku Islands. Functional structural archaeological remains integrated in the cultural unity of the social system as a symbolic interaction. Maluku Archipelago covers the two areas, namely Maluku and North Maluku. The problem this paper is how archaeological resources can show the interpretation of symbolic interaction. Archaeological remains (cultural resources); dolmen, caves, castles, old country/old settlement, menhirs, sultanate, Kapata / folklore is the basic structure of cultural understanding in the Maluku Islands. The goal is to know and understand the remains, archaeological remains were able to reconstruct the culture of human society Maluku Islands. Approach to research using library study. From the research that archaeological cultural resources is a symbolic interpretation of the interaction of a group of human society in a particular area. Sites sampled studies prove that archaeological cultural resources as a reflection of the people of Maluku Generally and certain areas in the Moluccas in particular.Sumberdaya budaya arkeologi di Kepulauan Maluku terdiri dari berbagai aspek, diantaranya Prasejarah, Sejarah, Islam, Kolonial dan Etnoarkeologi. Aspek-aspek tersebut dikategorisasikan untuk memudahkan pemetaan penelitian arkeologi di Kepulauan Maluku. Struktural fungsional tinggalan-tinggalan arkeologi terintegrasi dalam kesatuan sistem sosial budaya sebagai interaksi simbolik. Kepulauan Maluku berarti kita berbicara dalam dua wilayah, yaitu Maluku dan Maluku Utara. Permasalahan penulisan ini adalah bagaimana sumberdaya budaya arkeologis dapat menunjukan interprestasi interaksi simbolik. Tinggalan-tinggalan arkeologis (sumberdaya budaya); dolmen, gua, benteng, negeri lama/permukiman lama, menhir, kesultanan, kapata/folklore adalah struktur dasar pemahaman akan kebudayaan di Kepulauan Maluku. Tujuannya adalah untuk mengetahui dan memahami tinggalan-tinggalan arkeologis mampu merekonstruksi kebudayaan masyarakat manusia Kepulauan Maluku. Pendekatan penelitian menggunakan studi kepustakaan. Dari hasil penelitian bahwa sumberdaya budaya arkeologi merupakan suatu interprestasi interaksi simbolik suatu kelompok manusia masyarakat pada daerah tertentu. Situs-situs kajian penulis yang menjadi sampel membuktikan bahwa sumberdaya budaya arkeologi sebagai cerminan masyarakat Maluku Umumnya dan daerah tertentu di Maluku pada khususnya.